A manganese superoxide dismutase (MnSOD) from ark shell, Scapharca broughtonii: Molecular characterization, expression and immune activity analysis. Issue 2 (August 2015) - Zheng, Libing; Wu, Biao; Liu, Zhihong; Tian, Jiteng; Yu, Tao; Zhou, Liqing; Sun, Xiujun; Yang, Aiguo
Abstract Manganese superoxide dismutase (MnSOD) is one of the key members of the antioxidant defense enzyme family, however, data regarding to the immune function of MnSOD in mollusks still remain limited now. In this study, a full-length MnSOD cDNA was identified by rapid amplification of cDNA ends (RACE) method from cDNA library of ark shell Scapharca broughtonii (termed SbMnSOD). The cDNA contained an open reading frame (ORF) of 696 bp which encoded a polypeptide of 232 amino acids, a 5′-UTR with length of 32 bp and a 3′-UTR of 275 bp. Four putative amino acid residues (His-57, His-105, Asp-190 and His-194) responsible for manganese coordination were located in the most highly conserved regions of SbMnSOD and the signature sequence (DVWEHAYY) also existed in SbMnSOD. The deduced amino acid sequence of SbMnSOD shared high homology to MnSOD from other species. All those data revealed that the SbMnSOD was a novel member of the MnSOD family. The mRNA expression profiles of SbMnSOD in tissues of foot, gill, mantle, adductor muscle, hemocytes and hepatopancreas analyzed by quantitative real-time PCR (qRT-PCR) suggested the mRNA transcripts of SbMnSOD distributed in all the examined tissues. Importantly, Vibrio anguillarum challenge resulted in the increased expression of SbMnSOD mRNA with a regular change trend in all examined tissues, indicating SbMnSOD actively participated in the immune response process. What's more, further analysis on the antibacterial activity of the recombinant SbMnSOD showed that the fusion protein could remarkably inhibit growth of both Gram-positive and Gram-negative bacteria. The present results clearly suggested that SbMnSOD was an acute phase protein involved in the immune reaction in S. broughtonii.